Investıgatıon of The Expectatıons From Sports And Sports Centers For Dıfferent Varıables - Erdal Tasgın; Nazlı Deniz Öz; Ferhat Üstün; Metin Özlü (Türk Spor ve Egzersiz Dergisi)
The study was carried out at a special sports center in Konya. The subjects were 209 women and 274 men, totally 483 of whom were active in any of these sport centers and participated voluntarily in our study. Data in the study is obtained from “the Level of Expectation Level Scale of the Sports Centers” developed by Bingöl (2010). After obtaining information about the age, gender and duration of the sport before the scale application, “the Level of Expectation of Expectations from Sports Centers “ is applied to the same subjects. With this scale, it has been tried to determine the levels of expectations for physical development, personality development and health by means of sports and sports centers. 5-point Likert Scale was used for the scale consisting of 18 questions. Scale items were given with “1: Strongly Disagree, 2: Disagree, 3: Less Agree, 4: Agree,  5: Strongly Agree” options. According to the results of the study, the level of fulfillment of expectations in sports and sports centers was not significantly differentiated according to age (F(3-482)=1,220; P gt;0,05), In comparison with gender, it was seen that the level of meeting the expectations of male participants was higher than that of women (t(458)= -3,334; P lt;0,05). In addition, it was concluded that the rate of meeting the expectation levels of sportsmen who use gyms for 1-6 months is higher than those who use gyms for 1-3 years. (F(4-482)=3,107; P lt;0,05).